ClC-1 Inhibition as a Mechanism for Accelerating Skeletal Muscle Recovery After Neuromuscular Block in Rats - Marianne Skals; Martin Broch-Lips; Martin Brandhøj Skov; Anders Riisager; Judith Ceelen; Ole Bækgaard Nielsen; Sorin J. Brull; Hans D. de Boer; Thomas Holm Pedersen (Nature Communications)
Abstract Neuromuscular blocking agents are used commonly to induce skeletal muscle relaxation during surgery. While muscle relaxation facilitates surgical procedures and tracheal intubation, adequate recovery of muscle function after surgery is required to support pulmonary function, and even mild residual neuromuscular block increases the risk of severe postoperative pulmonary complications. While recovery of muscle function after surgery involving neuromuscular blocking agents can be monitored and, in addition, be accelerated by use of current antagonists (reversal agents), there is a clear clinical need for a safe drug to antagonize all types of neuromuscular blocking agents. Here, we show that inhibition of the skeletal muscle-specific chloride ion (Cl-) channel, the ClC-1 channel, markedly accelerates recovery of both single contraction (twitch) and, important physiologically, sustained (tetanic) contractions in a rat model mimicking neuromuscular blocking agent-induced muscle block used during surgery. This suggests ClC-1 inhibition as a mechanism for fast and efficacious recovery of neuromuscular function induced by any neuromuscular blocking agents.